(untitled) (Scientific journal of the Fergana State University, 2023)
A paper discusses the role of television in raising activity of population. Especially, the focus is given to highlighting a practical importance of programmes which are designed to form democratic thinking and raise political activity of population in Uzbekistan. Moreover, the paper indicates what kind of media population prefers to watch more and on the bases of the sociological survey the role of television in the life of population is shown. As well as, the role of television in raising a legal culture of population, highlighting their appeals and suggestions, and realization of social control is studied.